Guidelines of Meat Goat Production in the Three Southern Border Provinces of Thailand - Limcharoen, Somnuek; Trimanee, Sunee; Thaiburi, Narid; Jun-iad, Jamnong; Kochapakdee, Surasak (Princess of Naradhiwas University Journal, 2021)
This research aimed to study social and economic conditions, the need for meat goat production and problems, obstacles and suggestions of farmers aiming to develop guidelines for meat goat production in 3 southern border provinces of Thailand. Research study used a mixed-method design. The structured interviews were conducted with 396 meat goat farmers from 33,307 farmers located in the three border provinces, calculated with error data at 5%. The qualitative data were collected from 15 government officers working on providing supports and promoting meat goat farming, and the samples were derived from purposive sampling. Data were analyzed using descriptive statistics; frequency, percentage, mean, standard deviation, and Multiple Regression Analysis. The analysis revealed that meat goat farmers were Muslim local farmers. The main aim of the meat goat farming was for sales. The meat goat was sold as a whole. The average selling price was 3,806.70 baht per head. It was found that farmers’ need for promoting meat goat production was at a high level. The analysis of the relationship between socio-economic factors and the condition of meat goat farming were shown the correlation with meat goat production with statistically significant (P<0.01). The guidelines for promoting meat goat farming showed 4 significant factors related to communication as follows: 1) sources of information or message senders livestock officers (individual) and experts in the field of animal science must have expertise and knowledge in production meat goat, 2) messages or information about selecting breeding goats, parenting practice, food, animal feeding, prevention and treatment, 3) communication channels and media; organizing field trip to a successful meat goat farm, promoting knowledge through television, and setting up the farmer groups and 4) people who received the information or training; meat goat farmers, and the transfer of knowledge started from basic knowledge to technology and innovation of production meat goat, mainly by explanation combined with a real example, practice and demonstration.